Developing and understanding the use of patient reported outcomes in advanced renal disease - Pittman, Zoe C.L. (2020)
Introduction The number of patients receiving treatment for advanced chronic kidney disease (CKD) is increasing worldwide. Current treatments are imperfect and impose a number of restrictions on daily life, both physical and psychosocial. The psychosocial burdens of advanced CKD have been explored to varying degrees with the effects on quality of life and symptoms most extensively documented in cross sectional data. There are no data on changing symptoms over relatively short time periods or the factors that affect an individual patient’s interaction with the disease and its treatments.